Assessment of financing needs of SMEs in the Western Balkans countries. Country report: FYROM - Peter Hauser; Tatyana Dolgaya; Sorin Revenko; Michael Kortenbusch (European Investment Bank (EIB), 2016)
This report is one of a series of reports produced by Business & Finance Consulting GmbH (BFC) for European Investment Bank (EIB) as part of the project “Assessment of financing needs of SMEs in Western Balkans countries.” The series of reports includes individual reports on Albania, Bosnia and Herzegovina, Kosovo, Macedonia, Montenegro, and Serbia as well as a synthesis report which considers the results of all six reports. The purpose of the project is to assess the financing needs of SMEs in the Western Balkans and identify market failures that prevent SME access to finance. The project was carried out from October 2015 to April 2016 by a team of three experts from BFC. Onsite visits were conducted for each country in order to meet with representatives from financial institutions, development institutions, government organizations, and other relevant experts who can provide insights into the SME sector.
Keywords: 330; Unternehmensfinanzierung; KMU; Mazedonien